AERA OTL 2022 Special Issue Introduction - Xu, Qian; Richardson, Jennifer; Lowenthal, Patrick (Online Learning, 2022)
The American Educational Research Association (AERA) is a research society that “strives to advance knowledge about education, to encourage scholarly inquiry related to education, and to promote the use of research to improve education and serve the public good” (2022). The association aims to encourage educational research studies and promote the practical implications of research findings. With 12 divisions and more than 150 special interest groups (SIGs), AERA provides advanced information to generate connections across practitioners, the field’s leading researchers, and policymakers. AERA includes more than 25,000 members from 85 countries, including faculty, researchers, evaluators, graduate students, university deans, research directors, and higher education administrators. In 2022, the AERA annual meeting was both place-based in San Diego, California, and virtual, with the theme of “Cultivating Equitable Education Systems for the 21st Century”. As an influential special interest group (SIG) of AERA, the Online Teaching and Learning (OTL) SIG provides 200-plus members an informative platform to discuss and disseminate challenges and possibilities relating to online learning and teaching. For more information on OTL visit http://www.aera.net/SIG035/Online-Teaching-and-Learning-SIG-35. SIG OTL and the Online Learning Consortium (OLC) have maintained a long-standing collaboration to advance the theory and practice of online, blended, and digital learning. Since 2016, the Online Learning journal (OLJ), the official journal of OLC, has released a special issue to extend opportunities for SIG OTL members to contribute their expertise in online education research. The 10 papers selected for this issue represent diverse voices of educators and professionals sharing rigorous research and innovative topics using an array of research methods. They are arranged into three major categories: students’ cognitive and behavioral strategies in online environments; theoretical and practical implications of online learning and community; and students’ online learning experiences.